Jawabanmu

2014-09-09T21:41:27+07:00
1. \sqrt{25.5} + \sqrt{5} + \sqrt{25.3} = 5 \sqrt{5} + \sqrt{5} + 5 \sqrt{3} = 6 \sqrt{5} + 5 \sqrt{3} \\ 
\\ 
2. 3 \sqrt{4.7} + 4 \sqrt{7} - 3 \sqrt{7} = 3.2 \sqrt{7} + 4 \sqrt{7} - 3 \sqrt{7} = 6 \sqrt{7} + 4 \sqrt{7} - 3 \sqrt{7} = 7 \sqrt{7} 
\\ 
\\ 
3. 3 * \sqrt[3]{3} - 3 \sqrt[3]{27.3} = 3 \sqrt[3]{3} - 3 \sqrt[3]{3} = 0
Yang no 1 itu akar 25x3 , kenapa 3 nya yang keluar & jadi 3 akar 5? Bukannya jadi 5 akar 3?
iya maaf, sudah diganti. terimakasih koreksinya.
2014-09-09T21:43:48+07:00